Preparation method and application of anode material for electrocatalytic degradation
By uniformly coating SnO2-Sb sol on the FTO conductive glass, SnO2-Sb/FTO electrode material was prepared, which solved the problems of poor stability, high cost and complex process of existing electrode materials, achieved high efficiency and low energy consumption electrocatalytic oxidation effect, and reduced the risk of metal ion pollution.
Patent Information
- Application Number
- CN202411904446.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-01
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing electrode materials have poor stability, high cost, complex process and easy passivation during the electrocatalytic oxidation process. Especially when dealing with antibiotic wastewater, energy consumption is high and metal ion pollution risks are high.
The SnO2-Sb/FTO electrode material was prepared by using FTO conductive glass as the base material and the SnO2-Sb sol was uniformly coated by the sol-gel method. This method simplifies the process flow, reduces costs, and improves the mechanical strength and chemical stability of the electrodes.
SnO2-Sb/FTO electrode material significantly increases the oxygen evolution potential, reduces the electrochemical impedance, improves electrocatalytic activity and stability, has low energy consumption and long life, and when treating antibiotic wastewater, the energy consumption is lower, reducing the risk of metal ion pollution.
Smart Images

Figure CN119733501A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrode materials, specifically, to electrode materials used in electrocatalytic oxidation technology in wastewater treatment, and especially to a method for preparing and applying an anode material for electrocatalytic degradation. Background Art
[0002] Electrocatalytic oxidation technology, due to its high performance, simple operation, and environmental friendliness, is considered an effective method for removing refractory organic pollutants from water. In electrocatalytic oxidation technology, the performance of the electrode anode material is a key factor in determining the effectiveness of electrocatalytic oxidation and the removal of organic pollutants from wastewater. Common electrode materials such as platinum, boron-doped diamond (BDD), metal oxide electrodes (dimensionally stable anodes (DSA), and novel electrode materials, such as carbonaceous electrodes, can effectively remove organic pollutants from wastewater. Platinum electrodes, however, exhibit far inferior electrocatalytic oxidation performance to metal oxide electrodes. They suffer from disadvantages such as poor stability, the tendency of organic matter to polymerize and form films on their surfaces, and high cost, limiting their application and gradually phasing them out. Diamond films are expensive and complex to prepare, making them unsuitable for large-scale industrial treatment of antibiotic wastewater. Carbonaceous electrodes, including activated carbon fibers, carbon felt, carbon electrodes (such as graphite electrodes), and carbon nanotubes, offer advantages such as good conductivity, high chemical stability, and low cost. However, carbonaceous materials are highly susceptible to corrosion and have low strength. Especially when used as anodes, they react with evolved oxygen, leading to swelling and shedding.
[0003] DSA is one of the most widely used and promising electrode materials, widely used in many electrochemical industries, such as the chlor-alkali industry, water electrolysis, and metal electrowinning. Furthermore, scale-up experiments have successfully demonstrated the practicality of DSA electrodes in wastewater treatment. DSA electrodes primarily enhance stability and conductivity by coating the surface of a metal conductor with a non-corrosive metal oxide.
[0004] Currently, DSA anode materials primarily include SnO2, PbO2, RuO2, IrO2, Ta2O5, and their composites. Among them, tin dioxide (SnO2) is a wide-bandgap (3.6 eV) n-type semiconductor oxide with a high oxygen evolution overpotential and excellent electrocatalytic activity, making it a common anode material. To improve SnO2's conductivity at room temperature, antimony (Sb) is often doped into SnO2, resulting in excellent electrochemical performance.
[0005] SnO2-Sb in powder form cannot be used alone for electrocatalysis and needs to be loaded on a substrate. DSA generally uses Ti-based materials, which have the advantages of low loss rate and high catalytic activity compared to traditional electrode materials (such as platinum, lead, graphite, lead dioxide, etc.). However, during use, the matrix Ti easily generates oxide TiO2, which causes electrode passivation, thereby significantly reducing the conductivity of the electrode. It is also easy to cause the electrocatalytic layer to fall off, reducing the electrocatalytic activity, and thus increasing the energy consumption and cost of the entire degradation process. In order to improve the electrode performance, other matrix materials such as carbon-based are used in SnO2-Sb materials as the substrate of SnO2-Sb electrodes, but the preparation process of carbon-based materials is very complicated and the cost is relatively high. Summary of the Invention
[0006] The present invention provides a method for preparing an anode material for electrocatalytic degradation and its application, which can solve the above problems.
[0007] In order to solve the above problems, the technical solutions adopted by the present invention are as follows:
[0008] In a first aspect, the present invention provides a method for preparing an electrode anode material, comprising the following steps:
[0009] (1) Cleaning the FTO conductive glass;
[0010] (2) Prepare SnO2-Sb sol using concentrated hydrochloric acid, SnCl2·2H2O, Sb2O3 and ethanol;
[0011] (3) The SnO2-Sb sol is evenly coated on the FTO conductive glass in multiple times, and the FTO conductive glass is pre-dried after each coating operation;
[0012] (4) The FTO conductive glass coated with SnO2-Sb sol multiple times and pre-dried is dried for the final time to obtain a SnO2-Sb / FTO electrode, thereby completing the preparation of the electrode anode material.
[0013] Preferably, in step (1), the method for cleaning the FTO conductive glass is: ultrasonically treating the FTO conductive glass in acetone, ethanol and ultrapure water for 15 minutes in sequence, and then drying it.
[0014] Preferably, step (2) is specifically as follows: 5 ml of concentrated hydrochloric acid, 10 mmol SnCl2·2H2O and 0.25 mmol Sb2O3 are added to 50 mL of ethanol solution, mixed evenly, stirred at room temperature for 12 h, and aged for 24 h to obtain SnO2-Sb sol.
[0015] Preferably, in step (3), the FTO conductive glass is uniformly coated with SnO2-Sb sol 10 times.
[0016] Preferably, in step (3), each pre-drying operation is: drying at 100° C. for 10 minutes to form a dry gel film on the surface of the FTO conductive glass, and then drying at 450° C. for 15 minutes.
[0017] Preferably, in step (4), the last drying operation is continuous drying at 450° C. for 2 h.
[0018] In a second aspect, the present invention uses the electrode anode material prepared by the preparation method described in the first aspect as an electrocatalytic oxidation electrode anode.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] 1) FTO conductive glass is used as the substrate material. The FTO substrate has excellent mechanical strength and can withstand high temperatures and strong acid and alkali corrosion. Compared with Ti and carbon substrates, FTO material is more stable and is not restricted by calcination during electrode preparation, nor is it affected by the use of strong acids and alkalis. It also does not undergo anode passivation during use, extending the life of the electrode. Furthermore, compared with traditional Ti-based electrodes of the same specifications, the Ti substrate is 6.25 times more expensive than the FTO substrate, making it economical and practical, effectively reducing production costs in large-scale industrial applications.
[0021] 2) The SnO2-Sb coating significantly improves the electrode's oxygen evolution potential (OEP), lowers its electrochemical impedance, and increases its charge transfer efficiency. Experiments show that the SnO2-Sb / FTO electrode exhibits superior electrocatalytic activity and stability to existing FTO and SnO2 / FTO electrode materials, as well as higher than that of SnO2-Sb / Ti electrodes. In particular, the electrocatalytic performance remains stable after 15 cycles of repeated use, demonstrating its long lifespan in effectively removing pollutants from water.
[0022] 3) When the SnO2-Sb / FTO electrode prepared by the present invention is used to degrade tetracycline, the degradation efficiency is significantly improved, and the reaction rate constant is 0.144min - 1. Energy consumption is 13.63kW·h·kg - 1. Energy consumption is lower than other traditional electrode materials. This electrode material consumes less energy during the electrocatalytic degradation process, showing high environmental benefits. Especially when treating antibiotic wastewater, it can effectively reduce energy consumption and reduce environmental pollution.
[0023] 4) Compared to the complex etching pretreatment process required for Ti-based electrodes in the prior art, the FTO substrate used in the present invention only requires simple cleaning and drying, is easy to operate, and does not generate acid pollution. For carbon-based materials, their preparation process is relatively complex and costly, while the present invention uses a sol-gel method to prepare the SnO2-Sb coating, which is simple to process and can effectively reduce production difficulty and cost.
[0024] 5) The surface structure of the SnO2-Sb / FTO electrode prepared in the present invention is a fine porous network structure, which can increase the active sites on the catalyst surface, reduce the mass transfer distance between pollutants and free radicals, and promote the degradation of pollutants. This electrode material can effectively remove tetracycline from water in a relatively short time and still maintain a good degradation effect at a relatively low voltage.
[0025] 6) During the electrocatalytic degradation process, the SnO2-Sb / FTO electrode prepared in the present invention releases a very low concentration of metal ions, which is much lower than that of traditional Cu-SnO2-Sb / Ti electrodes and other metal-based electrode materials. This feature effectively reduces the risk of metal ion pollution to water quality and ensures the safety and environmental friendliness of the wastewater treatment process.
[0026] In order to make the above-mentioned objects, features and advantages of the present invention more clearly understood, embodiments of the present invention are given below and described in detail with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other relevant drawings can be obtained based on these drawings without paying any creative work.
[0028] Figure 1 is a bar graph showing the removal efficiency of tetracycline by the SnO2-Sb / FTO electrode prepared in the embodiment;
[0029] Figure 2 1 is a cyclic voltammogram of the SnO2-Sb / FTO electrode prepared in the embodiment during repeated removal of tetracycline;
[0030] Figure 3 is a scanning electron microscope image of the FTO conductive glass in the embodiment;
[0031] Figure 4 is a scanning electron microscope image of the SnO2-Sb / FTO electrode material in the embodiment;
[0032] Figure 5This is a scanning electron microscope image of the SnO2-Sb / Ti electrode material in the prior art;
[0033] Figure 6 This is a scanning electron microscope image of the SnO2–Sb–Ce / Ti electrode material of the prior art;
[0034] Figure 7 This is a scanning electron microscope image of the prior art Cu-Sb-SnO2 electrode material;
[0035] Figure 8 This is a scanning electron microscope image of the SnO2-Ce / biocarbon sheet electrode material of the prior art;
[0036] Figure 9 This is a comparison of the electrochemical properties of the SnO2-Sb / FTO electrode prepared in an embodiment of the present invention, the existing FTO conductive glass electrode, and the SnO2 / FTO electrode;
[0037] Figure 10 The electrocatalytic degradation of 5 mg·L was performed using SnO2-Sb / FTO and SnO2-Sb / Ti electrodes. -1 Comparative chart of the effects of tetracycline;
[0038] Figure 11 This is a comparison of the electrochemical properties of SnO2-Sb / FTO and SnO2-Sb / Ti electrodes. DETAILED DESCRIPTION
[0039] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments.
[0040] The present invention provides a method for preparing an anode material (SnO2-Sb / FTO) for electrocatalytic degradation, which is as follows:
[0041] FTO conductive glass was ultrasonically treated in acetone, ethanol, and ultrapure water for 15 minutes, dried, and set aside. 5 mL of concentrated hydrochloric acid, 10 mmol of SnCl2·2H2O, and 0.25 mmol of Sb2O3 were added to 50 mL of ethanol solution, mixed thoroughly, stirred at room temperature for 12 hours, and aged for 24 hours to obtain a SnO2-Sb sol. The sol was evenly coated on the pretreated FTO conductive glass and dried at 100°C for 10 minutes to form a xerogel film on the FTO conductive glass surface. The film was then dried at 450°C for 15 minutes. This process was repeated 10 times, followed by heating at 450°C for 2 hours to obtain a SnO2-Sb / FTO electrode.
[0042] In this embodiment, FTO has high mechanical strength and excellent chemical stability, is resistant to high temperatures, and can also resist corrosion from strong acids and alkalis. Therefore, FTO is selected as the anode material matrix for electrocatalytic oxidation, and SnO2-Sb is impregnated and coated on the FTO surface using a simple sol-gel method, thereby preparing a new anode material with good electrocatalytic performance and good stability.
[0043] As can be seen from the preparation process, the present embodiment uses commercial FTO conductive glass to prepare electrodes, and the pretreatment process of the substrate (FTO conductive glass) is very simple, requiring only simple rinsing and drying. If a Ti substrate is used in the prior art, it must undergo etching pretreatment (polishing and polishing the titanium sheet, performing surface degreasing and oxalic acid etching), which is a time-consuming and labor-intensive step and also produces acid pollution. If a carbon-based material is used as in the prior art, different carbon-based substrates use different raw materials, and the preparation process is also different, and the preparation process is relatively complex and affects the stability of the substrate properties.
[0044] In the preparation of the active layer, the embodiment of the present invention uses only SnO2-Sb sol, which is simpler and more convenient than the preparation process of doping more elements.
[0045] The cost of preparing the electrode anode material (SnO2-Sb / FTO electrode) in this example is low: FTO conductive glass is relatively inexpensive. Using the same base material specifications, the cost of a Ti substrate is 6.25 times that of an FTO electrode. The cost of the raw materials for carbon-based materials is also relatively high. Therefore, from an application perspective, the FTO substrate is more cost-effective.
[0046] The electrode anode material (SnO2-Sb / FTO electrode) prepared in this embodiment has good stability: Figure 1 As shown in Figure 2, the SnO2-Sb / FTO electrode still has a good removal efficiency for tetracycline after being reused 15 times. Figure 2 It can be seen that there is no obvious change in the electrocatalytic oxidation performance of the electrode material.
[0047] The SnO2-Sb / FTO electrode prepared in this example has good electrocatalytic activity:
[0048] like Figure 4 As shown, the surface structure of SnO2-Sb / FTO electrode is a very fine porous network structure. Figure 3 The electrode material prepared by the FTO conductive glass substrate and other substrates of the prior art ( Figure 5 、 Figure 6 、 Figure 7 and Figure 8), this loose spatial structure can effectively promote the generation of active free radicals, and is conducive to the attachment of pollutants to the surface of the catalyst, reducing the mass transfer distance between pollutants and free radicals, and promoting the degradation of pollutants.
[0049] Combine Figure 9 As shown, the SnO2-Sb / FTO electrode prepared in this example is analyzed and compared with the FTO conductive glass and SnO2 / FTO electrode:
[0050] As we all know, the higher the oxygen evolution potential (OEP), that is, the higher the potential required for the electrode to undergo oxygen evolution reaction (OER), which can inhibit the generation of molecular oxygen from active free radicals such as OH and enhance the free radical oxidation ability of organic matter. Figure 9 Figure (a) shows the LSV curves of the three electrode materials at a scan rate of 100 mv / s, from which their OEPs are obtained. The OEP value of the SnO2-Sb / FTO electrode (2.30 V vs. SCE) is higher than that of the FTO and SnO2 / FTO electrodes (2.14 V and 2.11 V vs. SCE), indicating that the loading of SnO2-Sb significantly improves the electrode's OEP. Compared with SnO2-Sb electrodes on other substrates, the OEP values of the SnO2-Sb / FTO electrode are also significantly higher than those of the SnO2-Sb / ACFs electrode, SnO2-Sb / Ti electrode, SnO2-Sb-Ce / Ti electrode, and SnO2-Sb electrode on stainless steel (1.96 V, 2.01 V, 1.95 V, and 1.82 V vs. SCE).
[0051] Figure 9 (b) shows the EIS Nyquist spectra of FTO, SnO2 / FTO, and SnO2-Sb / FTO electrodes. The electrochemical impedance of the electrode is positively correlated with the radius of the EIS arc, that is, the smaller the arc radius, the lower the resistance value. The results show that compared with the original FTO electrode, the charge transfer resistance of the electrode is reduced after loading with SnO2-Sb. The radius of the SnO2-Sb / FTO electrode is the smallest, indicating that it has the lowest charge transfer resistance. This is because the introduction of Sb can significantly improve the conductivity of tin oxide.
[0052] The lower the self-corrosion potential, the easier it is for metal oxides to release or gain electrons in electrochemical reactions, thus showing better performance in the catalytic process. Figure 9 From the Tafel curves of the electrodes in (c), it can be seen that the self-corrosion potential of the SnO2-Sb / FTO electrode (-0.42 V vs SCE) is the lowest compared to the FTO and SnO2 / FTO electrodes (-0.36 V and -0.28 V vs SCE). This indicates that the SnO2-Sb / FTO electrode is more likely to release or gain electrons during electrochemical reactions, which may lead to better performance of the electrode in the catalytic process.
[0053] To evaluate the electrode reaction activity, the CV curves of each electrode were measured at a scan rate of 100 mv / s. Figure 9 From the CV curve of the electrode in (d), it can be seen that the oxidation peak current of the SnO2-Sb / FTO electrode (6.79 mA) is much higher than that of the FTO electrode (3.45 mA), which indicates that the loading of SnO2-Sb can effectively improve the electrochemical reaction activity of the FTO electrode and promote the generation of active free radicals such as ·OH.
[0054] With SnO2-Sb / FTO electrode as anode, graphite electrode as cathode, and SCE as reference electrode, the three electrodes were immersed in 50 mL of 5 mg·L sodium sulfate solution as supporting electrolyte. -1 In tetracycline solution, the distance between the cathode and anode electrodes was 2 cm, and electrocatalytic degradation was carried out in constant current mode at room temperature. Tetracycline was completely removed within 25 minutes, and the first-order reaction rate constant was 0.144 min -1 , energy consumption is 13.63kW·h·kg -1 However, the degradation rate of tetracycline by SnO2-Sb / FTO electrode prepared under the same conditions was only 78.5% in 25 minutes.
[0055] The SnO2-Sb / FTO electrode prepared in the embodiment of the present invention was compared with other electrodes reported in the prior art for the electrocatalytic degradation of tetracycline. The electrocatalytic degradation reaction rate constant was higher and the energy consumption was lower. As shown in Table 1, it can be seen that the degradation rate constant of tetracycline by the SnO2-Sb / FTO electrode was significantly higher than that by the Ti-based electrode, and the energy consumption was significantly lower than that by the Ti / Ti4O7 electrode and the Ti / SnO2-Sb electrode. Although the efficiency of tetracycline degradation by the Cu-SnO2-Sb / Ti electrode was higher, its energy consumption was much higher than that of the present electrode, and the cost of preparing the electrode was lower. In addition, after the degradation of the SnO2-Sb / FTO electrode, the concentrations of leached Sn and Sb ions were determined to be 0.02 and 0.08 μg L, respectively. -1 , which is lower than that of Cu-SnO2-Sb / Ti electrode (Sn: 13.0 μg L -1 and Sb: 4.5 μg L -1 ) two to three orders of magnitude.
[0056] Table 1
[0057]
[0058] like Figure 10 As shown in the figure, the SnO2-Sb / FTO and SnO2-Sb / Ti electrodes prepared in the embodiment of the present invention were electrocatalytically degraded to 5 mg·L -1Tetracycline, it can be seen that SnO2-Sb / FTO has a significantly better degradation effect on tetracycline.
[0059] Figure 11 The following is a comparison of the electrochemical properties of SnO2-Sb / FTO and SnO2-Sb / Ti electrodes, where Figures (a), (b), and (c) show the EIS Nyquist spectra, LSV curves, and voltage-time curves of the SnO2-Sb / Ti and SnO2-Sb / FTO electrodes, respectively. As can be seen from Figure (a), the radius of the SnO2-Sb / Ti electrode is smaller than that of the SnO2-Sb / FTO electrode, that is, the charge transfer resistance of the SnO2-Sb / Ti electrode is lower. However, the comparison of the LSV curves in Figure (b) shows that the OEP value of the SnO2-Sb / FTO electrode (2.30V vs SCE) is much higher than that of the SnO2-Sb / Ti electrode (1.78V vs SCE), indicating that the SnO2-Sb / FTO electrode has a relatively higher electrocatalytic oxidation ability. During the electrolysis process using SnO2-Sb / Ti electrodes, we observed a large number of bubbles on the anode surface, indicating that a significant oxygen evolution reaction occurred during the electrolysis process. This, to a certain extent, reduced the current efficiency of the electrocatalytic oxidation of organic matter on the electrode surface, thereby affecting the degradation effect. At the same time, Figure (c) shows that using Ti as a substrate, in a 0.1M sodium sulfate solution, using a current density of 1.25mA·cm 2 In this case, the potential increases with time, which may affect the stability and life of the electrode material. In comparison, with FTO as the substrate, the voltage of the entire system is more stable.
[0060] In summary, the present invention utilizes FTO conductive glass as a substrate and loads SnO2-Sb material to produce an electrode material with excellent electrochemical catalytic performance. This electrode has the advantages of simple preparation, low cost, low energy consumption, good stability, and good reusability. Using SnO2-Sb / FTO electrodes for electrocatalytic oxidation has great potential for removing organic pollutants from wastewater.
[0061] The foregoing description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Those skilled in the art will readily appreciate that various modifications and variations of the present invention are possible. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention are intended to be within the scope of protection of the present invention.
Claims
1. A method for preparing an anode material for electrocatalytic degradation, characterized in that: The following steps are involved: (1) Cleaning the FTO conductive glass; (2) SnO2-Sb sol was prepared using concentrated hydrochloric acid, SnCl2·2H2O, Sb2O3 and ethanol; (3) The SnO2-Sb sol is uniformly coated on the FTO conductive glass for multiple times, and the FTO conductive glass is pre-dried after each coating operation; (4) The FTO conductive glass coated with SnO2-Sb sol for multiple times and pre-dried is dried for the final time to obtain a SnO2-Sb / FTO electrode, thereby completing the preparation of the electrode anode material.
2. The preparation method according to claim 1, characterized in that: In step (1), the method for cleaning the FTO conductive glass is: ultrasonically treating the FTO conductive glass in acetone, ethanol and ultrapure water for 15 minutes in sequence, and then drying it.
3. The preparation method according to claim 1, characterized in that: Step (2) is specifically as follows: 5 ml of concentrated hydrochloric acid, 10 mmol SnCl2·2H2O and 0.25 mmol Sb2O3 are added to 50 mL of ethanol solution, mixed evenly, stirred at room temperature for 12 h, and aged for 24 h to obtain SnO2-Sb sol.
4. The preparation method according to claim 1, characterized in that: In step (3), the FTO conductive glass was uniformly coated with SnO2-Sb sol 10 times.
5. The preparation method according to claim 1, characterized in that: In step (3), each pre-drying operation is: drying at 100° C. for 10 min to form a dry gel film on the surface of the FTO conductive glass, and then drying at 450° C. for 15 min.
6. The preparation method according to claim 1, characterized in that: In step (4), the last drying operation is to continue drying at 450° C. for 2 h.
7. Use of the electrode anode material prepared by the preparation method according to any one of claims 1 to 6 as an electrocatalytic oxidation electrode anode.